The end of the American challenge? - Jacques Pelkmans (Intereconomics, 1982)
“Fifteen years hence not Europe will be the third industrial power in the world, after the United States and the USSR, but American industry in Europe” Servan-Schreiber wrote 1967 in his “The American Challenge”. Now those fifteen years are past. What has happened really?
Keywords: 330; Foreign Investiment